Scaffolded reaching experiences encourage grasping activity in infants at high risk for autism - Libertus, Klaus; Landa, Rebecca J. (Frontiers in Psychology, 2014)
Recent findings suggest impaired motor skill development during infancy in children later diagnosed with autism spectrum disorders (ASD). However, it remains unclear whether infants at high familial risk for ASD would benefit from early interventions targeting the motor domain. The current study investigated this issue by providing 3-month-old infants at high familial risk for ASD with training experiences aimed at facilitating independent reaching. A group of 17 high-risk (HR) infants received 2 weeks of scaffolded reaching experiences using “sticky mittens,” and was compared to 72 low-risk (LR) infants experiencing the same or alternative training procedures. Results indicate that HR infants – just like LR infants – show an increase in grasping activity following “sticky mittens” training. In contrast to LR infants, evidence that motor training encouraged a preference for faces in HR infants was inconclusive.